Approaches to rhythm control: Impact of electrical cardioversion versus pharmacological management on left atrial size and systolic performance in atrial fibrillation and flutter - Emir Bećirović; Minela Bećirović; Amir Bećirović; Lejla Tupković Rakovac; Amira Jagodić Ejubović; Begajeta Čaušević; Malik Ejubović; Aida Ribić; Lamija Ferhatbegović; Ammar Brkić; Semir Hadžić; Maida Skokić; et al. (Medicinski glasnik, 2025)
Aim: To compare the impact of electrical cardioversion (ECV) and pharmacological cardioversion (PCV) on left atrial size (LA) and left ventricular ejection fraction (LVEF), as well as to identify predictors of rhythm disorder recurrence in patients with atrial fibrillation (AF) or atrial flutter (AFL). Methods: A prospective observational cohort study was conducted on 105 patients with persistent AF or AFL at the University Clinical Centre Tuzla. The patients were divided into two groups: 53 underwent ECV and 52 received PCV. Demographic and clinical data, including ECG and transthoracic echocardiography, were collected. Follow-up assessments were conducted at 7 days, 1 month, and subsequently every 3 months for a year. Results: Baseline characteristics were similar between the groups. Recurrence of rhythm disorder within one year was observed in 52.4% of cases, with ECV showing a slightly lower, though not significantly different, primary failure rate at 7 days compared to PCV (13.2% vs. 23.1%). Significant predictors of recurrence included longer duration of disorder (p<0.001), hypertension (p=0.016), lack of pre-cardioversion amiodarone (p=0.027), and larger LA (p<0.001). Both ECV and PCV significantly reduced LA over time, with no significant differences in LVEF between groups. Conclusion: Both ECV and PCV are effective in restoring sinus rhythm, with a trend towards lower recurrence in the ECV group. Predictors such as disorder duration, hypertension, lack of pre-cardioversion amiodarone, and LA should be considered when planning cardioversion to optimize patient outcomes.
Keywords: amiodarone; arrhythmia; atrial enlargement; ejection fraction; hypertension; therapy.